Examining the Relationship between Employee Well-Being and Retention with Mediating Effect of Job Satisfaction among Generation Z - Elangovan, Sariveni; Rodzalan, Shazaitul Azreen; Sariyon, Noraini (Journal of Techno-Social, 2025)
The employee turnover rate increases drastically. Since employee turnover is rising drastically, keeping current employees is essential to the success of an organization. Employee well-being is an essential factor of retention, particularly for Generation Z, who frequently want workplaces that are flexible. However, because of Industry 4.0, a lot of organizations are moving to digital workplaces. Employee morale, productivity, and general performance are all negatively impacted by job or well-being dissatisfaction, which increases turnover. Therefore, this study aims to examine the relationship between employee well-being and employee retention with mediating effect of job satisfaction in digital workplace among Generation Z. The employee well-being factors is measured based on PERMA theory. The targeted respondents for this study are Generation Z who are working at manufacturing industries in Johor Bahru. Data was collected and analyzed quantitatively using Preacher and Hayes mediation analysis, SPSS, and Spearman correlation. The findings indicate that there is a positive relationship between employee retention and employee well-being and mediated by job satisfaction. Data was collected and analyzed quantitatively using Preacher and Hayes mediation analysis, SPSS, and Spearman correlation. This research offers useful insights on how well-being efforts might enhance job satisfaction and retention for stakeholders, including manufacturing industries and Generation Z employees.